Symmetry as tactics of solving mathematical problems - Elijio, Aistė; Malijonytė, Dovilė (Lietuvos matematikos rinkinys, 2012)
The article explores symmetry as tactics in solving various mathematical problems. Although in Mathematics curriculum while learning about Geometry, symmetry is taught and simple straightforward exercises are solved, it is argued that the application of symmetry could be much wider. It is especially useful as a strategy in solving non-standard math problems. The article presents examples of the use of such tactics as well as results from the experiment on the use of symmetry at school.